2007
DOI: 10.1523/jneurosci.4396-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

β-Site Amyloid Precursor Protein Cleaving Enzyme 1 Levels Become Elevated in Neurons around Amyloid Plaques: Implications for Alzheimer's Disease Pathogenesis

Abstract: ␤-Site amyloid precursor protein cleaving enzyme 1 (BACE1) (␤-secretase) initiates generation of ␤-amyloid (A␤), which plays an early role in Alzheimer's disease (AD). BACE1 levels are increased in postmortem AD brain, suggesting BACE1 elevation promotes A␤ production and AD. Alternatively, the BACE1 increase may be an epiphenomenon of late-stage AD. To distinguish between these possibilities, we analyzed BACE1 elevation using a highly specific BACE1 antibody, BACE-Cat1, made in BACE1Ϫ/Ϫ mice, which mount a ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

52
362
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(416 citation statements)
references
References 61 publications
52
362
1
1
Order By: Relevance
“…However, important distinctions between the two fragments could exist regarding their neuronal production and secretion sites, which in turn would determine their sites of biological activity. BACE1 is predominantly localized in endosomes of the soma and the presynaptic terminal (4,17,30,52), although ADAM8 is likely found on the plasma membrane. We determined that BACE1 and CHL1 co-localize in growth cones and terminals of hippocampal mossy fibers and OSN axons (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, important distinctions between the two fragments could exist regarding their neuronal production and secretion sites, which in turn would determine their sites of biological activity. BACE1 is predominantly localized in endosomes of the soma and the presynaptic terminal (4,17,30,52), although ADAM8 is likely found on the plasma membrane. We determined that BACE1 and CHL1 co-localize in growth cones and terminals of hippocampal mossy fibers and OSN axons (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…dentate gyrus granule cells, which project axons (mossy fibers) to CA3 pyramidal neurons. Importantly, mossy fiber terminals exhibit robust expression of BACE1 (17,30).…”
mentioning
confidence: 99%
“…Although specific details of amyloid pathology such as plaque age of onset, size and regional distribution, and Aβ species content vary depending on the line, APP‐overexpressing mice recapitulate aspects of cerebral Aβ accumulation, including production and deposition of Aβ and associated neuroinflammation (microgliosis and astrogliosis). In some cases, downstream pathologic consequences of Aβ deposition in overexpressing mice, such as tau hyperphosphorylation, formation of dystrophic neurites, loss of synaptic markers, and the accumulation of BACE1 (Zhao et al , 2007), appear similar to those observed in AD. Other effects of Aβ deposition in overexpressing mice may also be relevant to AD.…”
Section: Studies On First‐generation Mouse Modelsmentioning
confidence: 98%
“…These behavioral deficits are observed concomitant with the onset of hippocampal CA1 synaptic dysfunctions such as reduced basal transmission and long-term potentiation (LTP: a synaptic plasticity model for learning and memory) (Kimura and Ohno, 2009). Furthermore, 5XFAD mice begin to exhibit elevations in expression levels of the b-secretase (b-site APP cleaving enzyme 1: BACE1), which is responsible for initiating the production of Ab, at 6-9 months of age (Devi and Ohno, 2010b;Ohno et al, 2007;Zhang et al, 2009;Zhao et al, 2007), as observed in sporadic AD brains (Fukumoto et al, 2002;Li et al, 2004;Yang et al, 2003). To rigorously test the therapeutic potential of 7,8-DHF, we used the advanced stage of 5XFAD transgenic mice (12-15 months of age) that is more relevant to clinic AD cases manifesting robust amyloidosis, BACE1 elevations, BDNF-TrkB dysfunction, and profound memory impairments.…”
Section: Introductionmentioning
confidence: 99%